Can placebos reduce intrusive memories?. (November 2022) - Kube, Tobias; Kirsch, Irving; Glombiewski, Julia A.; Herzog, Philipp
Abstract: After traumatic experiences, intrusive memories can flash back and evoke significant distress. Here, we investigated whether the frequency and severity of intrusions can be reduced by the provision of placebo. After the (online) exposure to the trauma-film paradigm, healthy participants ( N  = 112) received deceptive placebo (DP), open-label placebo (OLP), or no treatment. In the DP group, participants were led to believe to receive a dopamine-modulating drug, which was supposed to disrupt the consolidation of traumatic memories, although they in fact received the same placebo tablets as the OLP group for one week. The results show that the groups did not differ in the frequency of intrusive memories after one week. However, participants receiving OLP reported a significantly reduced intensity of intrusions as compared to DP. Across groups, negative expectations about the intensity and controllability of intrusions were associated with a higher frequency of intrusions, higher distress, higher burden, and more negative appraisal. The results suggest that expectations play an important role in the emergence of intrusive memories and that some of the disabling aspects of intrusive memories can be reduced by placebo. This may carry clinical potential because placebos are an accessible, cost-effective intervention to reduce the risk of intrusive memories. Highlights: There is a need to develop accessible and cost-effective interventions for PTSD. We tested whether the occurrence of intrusive memories can be reduced by placebo. Open-label placebo, but not deceptive placebo, reduced the intensity of intrusions. Negative expectations were related to more frequent and severe intrusions. Open-label placebos may have the potential to reduce risk factors of PTSD.